Development of wordwall educational games based on Peo-Heda local wisdom to improve children's social skills - Konstantinus Dua Dhiu; Wilibaldus Bhoke (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This research aims to develop the GAULL (Wordwall Educational Game) Puzzle Application, based on the local culture of Woe Are